Development of Three Tier Online Test Diagnostic of Misconception for Topic Free Fall Motion - Nisa, Etik Khoirun; Habibbulloh, Muhammad (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to develop an online Three Tier Test Diagnostic of misconception in topic free fall motion. Methodology: This research is development research using a development model 4D by Thiagarajan (Define, Desain, Development, and Dissemination). However, the research is only limited to the Development stage because the research objectives have been achieved. The data collection instrument is a media expert validation questionnaire. The research data includes quantitative data in the form of expert validator evaluations and qualitative data in the form of comments and suggestions given by expert validators. Main Findings: The results showed that the product three tier online test diagnostic was feasible to use based on expert validation with a very feasible category. The resulting product has five item questions and consist of three tiers. The first tier is multiple choice questions, second is reason for answering question, and third tier is curiosity response index (CRI). Novelty/Originality of this study: The novelty of this research is uses an online test. This is expected to be able to support the effectiveness of further research by researchers.